ECONOMIC REFORM AND STRUCTURAL IN ARAB AGRICULTURAL - Salim Y. Al-Niaamy (Mesopotamia Journal of Agriculture)
Economic stabilization and structural adjustments are among the important programs adopted by economic policies in the developing and Arabic countries. These programs deal with the structural imbalances in economic sectors. In this study concentration is laid upon dealing with imbalance in agricultural sector in Yemen, Syria and Saudi Arabia. These countries are selected as a sample representing the Arabic countries in their intellectual and source differences. Similar structural variables with some differences in the economic model are also used where due to the priority of dealing with these economic imbalances in agricultural sectors in each of these countries have been differences in the nature of dealing with these imbalances. Analysis had depended on acomparison between pre and post economic reform for the model of using similar variables for the two periods to identify the negative or positive changes in these variables after adopting reform programs. The study has showed that there were positive indicators in some variables after adopting economic reform while some of them remained unchanged, as in Yemen, for example. For Syria this approach has some negative effects especially for type of change in agriculture contribution rate in gross domestic production. In Saudi Arabia where no change has been noticed in type of change in agricultural product value (structural variable) positive aspects of adopting reform programs include the change of index number of food products prices and the index number of agricultural production per capita from non-significant to significant variables